Budding metaphors: Input-output effects in metaphor production - Dorota Katarzyna Gaskins; Gabriella Rundblad (PLoS ONE, 2025)
This paper presents a longitudinal analysis of input-output effects in the production of metaphoric expressions by children aged two to five. The group case-study design adopted in this project involved longitudinally sampled corpora of naturalistic conversations between six English- and five Polish-speaking children and their primary caregivers, analysed by means of a usage-based approach to metaphor identification in child speech (UBAMICS) recently developed for English and adapted for Polish. Overall, 146,103 expressions were traced back to underlying metaphorical mappings in the densely sampled English corpora, and 22,909 in the less densely sampled Polish corpora. The data demonstrate clear input-output effects in the acquisition of conventional metaphoric expressions, both for primary conceptual metaphors that bring abstract domains closer to our embodied experience (e.g., Your gran is such a warm person) and for resemblance metaphors that map properties of familiar concepts onto those of less familiar ones based on their physical or behavioral resemblance (e.g., You’re my treasure). They are discussed in the context of two leading theories: Conceptual Metaphor Theory and Pragmatic Theory, highlighting to what extent they can account for our findings. A novel Usage-Based account is proposed to explain those findings which are problematic or when viewed through the lens of the current accounts of metaphor acquisition.